Ethanolic extract of Commiphora myrrha gum-resin promotes therapeutic compound accumulation in Achillea fragrantissima under in vitro culture - Khattab, Mohamed S.; Al Dayel, Munirah F.; El Sherif, Fadia (Frontiers in Plant Science, 2026)
IntroductionAchillea fragrantissima is valued for its broad spectrum of secondary metabo-lites with notable therapeutic potential. This study examined the influence of an ethanolic extract of Commiphora myrrha gum-resin on in vitro shoot growth, callus formation, and the effect of compound composition in A. fragrantissima.Material and methodsShoot-tip and root-segment explants were cultured on Murashi-ge and Skoog (MS) medium supplemented with filter-sterilized C. myrrha ethanolic extract at 0.5, 1.0, and 2.0 g·L-1, alongside control treatment. Plant responses, including growth parameters, callus induction percentage and biomass, photosynthetic pigments, and me-tabolite composition, were assessed after one month of in vitro culture. GC–MS analysis was performed on the C. myrrha extract and on methanolic extracts of A. fragrantissima plantlets and callus tissues obtained from different treatments.ResultsGC–MS analysis of the ethanolic extract of C. myrrha identified 66 phytochemi-cal compounds dominated by sesquiterpenes—particularly 2,5,8-trimethyl-1-nonen-3-yn-5-ol, curzerene, myrcenol, germa-cra-1(10),4,11(13)-trien-12-oic acid, and several oxygenated sesquiterpenes—indicating a rich pool of bioactive, growth-promoting constituents. Shoot-tip and root-segment ex-plants showed the strongest responses to C. myrrha extract at specific concentrations. The highest concentration tested (2.0 g·L-1) produced the most shoots and the greatest accu-mulation of photosynthetic pigments, including total chlorophyll and carotenoids. In contrast, the lowest concentration (0.5 g·L-1) promoted the longest shoots, the highest fresh weight, and the greatest number of leaves. Callus formation from shoot tips was also highest at 0.5 g•L-1, while root-derived callus reached full induction at both 0.5 and 2.0 g·L-1. Both shoot-tip plantlets and root-derived callus showed notable modifications in their bioactive constituents. Several bioactive constituents were notably elevated (e.g., de-sulphosinigrin, thymidine, 4H-pyran-4-one derivatives, and fatty acid derivatives).DiscussionDistinct tissue-specific patterns emerged, shoot tips accumulated a wider range of aromatic and therapeutic compounds, whereas callus tissue was enriched in fat-ty acids. These findings suggest that C. myrrha extract functions as a natural biostimulant and elicitor, providing a sustainable approach for producing metabolite-rich A. fragrantis-sima material with potential pharmacological applications.